Limits implemented by parents in the child-rearing of 3 to 6 years old - Ares, María Soledad (2015)
The present research work aims to describe characteristics of the Limits implemented by parents in the child-rearing of 3 to 6 years old. For that purpose, a qualitative empirical method and the design of grounded theory was used. To this end was selected a sample of 10 fathers and 10 mothers between 25 to 35 years old, belonging to the middle class and residents of Buenos Aires Province, Argentina.Some of the findings coincided with what was stated in previous research. However certain variables and habits were discovered which nowadays have relevance, such as new objectives which parents consider at the moment of set limits or negotiation as a constant in the interaction.